(untitled) (Repertorio Científico, 2020)
Due to its location, Central America is exposed to multiple threats that, with the combination of threats from each of the countries, make the region considered high risk. For this reason, the purpose of this work was to examine the evolution and challenges of disaster management in Central America. Joint efforts in risk management date back to the 1990s, with which strategies and guidelines for disaster prevention and mitigation have been developed. Although there is significant progress, there are still challenges and situations to be resolved, which is reflected in the fragility of societies in the face of frequent and new threats.